2018
DOI: 10.1038/s41416-018-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 blocks SESN1/AMPK/PGC-1α/UCP2 axis increasing mitochondrial O2ˉ· production in cancer cells

Abstract: Background The TP53 tumor suppressor gene is the most frequently altered gene in tumors and mutant p53 gain-of-function isoforms actively promote cancer malignancy. Methods A panel of wild-type and mutant p53 cancer cell lines of different tissues, including pancreas, breast, skin, and lung were used, as well as chronic lymphocytic leukemia (CLL) patients with different TP53 gene status. The effects of mutant p53 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…In this regard, it has been demonstrated that mutant forms of p53 can inhibit PGC-1α function [137]. Furthermore, we showed that the inhibition of PGC-1α by mutant p53 is linked to the downregulation of mitochondrial UCP2 expression, favoring a determining ROS increase [8].…”
Section: Regulation Of Ros-related Transcription Factors By Mutant P5mentioning
confidence: 66%
See 4 more Smart Citations
“…In this regard, it has been demonstrated that mutant forms of p53 can inhibit PGC-1α function [137]. Furthermore, we showed that the inhibition of PGC-1α by mutant p53 is linked to the downregulation of mitochondrial UCP2 expression, favoring a determining ROS increase [8].…”
Section: Regulation Of Ros-related Transcription Factors By Mutant P5mentioning
confidence: 66%
“…Many years of research unveiled that GOF p53 mutations support tumor progression by regulating a complex overview of diversified pathways associated with: adaptive metabolic switch in responses to cancer-related stressing conditions; reduced response to chemotherapy; promotion of migration, invasion, and metastasis [6,7]. Cancer cells expressing mutant p53 show high levels of ROS compared with wild type p53 cells and we and others discovered that GOF mutant p53 isoforms, among the other abilities, contribute to enhance ROS levels in cancer cells through a coordinated regulation of several redox-related enzymes and signaling pathways, thus favoring cancer cell growth [8].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations